Associations of linear growth and weight gain in the first 2 years with bone mass at 4 years of age in children in Dhaka, Bangladesh - Maimuna Gias; Huma Qamar; Farzana Fariha; Abdullah Al Mahmud; Prakesh Shah; Steven A Abrams; Daniel E Roth; Karen M O’Callaghan (Public Health Nutrition)
Abstract